2018
DOI: 10.1002/adem.201701164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Random Void Defects on the Mechanical Behavior of C/C Braided Composites

Abstract: Carbon/carbon (C/C) composites are widely used in engineering due to their superior mechanical performance. However, manufacturing defects, such as voids and micro-cracks, seriously affect the C/C material and may initiate microstructural damage. In this paper, finite element models with random void defects are constructed to analyze the progressive damage behavior of C/C braided composites subjected to uniaxial tension. Because Hashin's criteria may not accurately predict the onset of failure for the braided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The porous nature of the CNT film or fiber preform is generally detrimental for applications where high strength and high electrical conductivity are needed. ,, As a result, the densification as a post-treatment is universally applicable for both pure CNT assemblies and CNT composites to eliminate as many voids and pores as possible. However, for CNT/C composites, the densification process is complicated.…”
Section: Mechanical Reinforcement Mechanism Of Cnt/c Compositesmentioning
confidence: 99%
“…The porous nature of the CNT film or fiber preform is generally detrimental for applications where high strength and high electrical conductivity are needed. ,, As a result, the densification as a post-treatment is universally applicable for both pure CNT assemblies and CNT composites to eliminate as many voids and pores as possible. However, for CNT/C composites, the densification process is complicated.…”
Section: Mechanical Reinforcement Mechanism Of Cnt/c Compositesmentioning
confidence: 99%
“…They found that 2% increment in voids reduced 12.7% flexural strength and showed that void’s size has a major role in reducing strength and initiate delamination. Xu et al modeled the FE model with random voids effects and presented the void in the FE model through the monte-carlo algorithm, and used fracture energy criteria to take them into account for strength prediction [ 31 ]. They proposed that voids have more effect on elastic modulus and tensile strength of matrix than fiber yarn in braided C/C composites.…”
Section: Failure Theoriesmentioning
confidence: 99%
“…Air voids are the most common influenceable flaws, significantly affecting the application and eligibility of composite structures [ 30 ]. Experimental studies showed that voids and microcracks are the common known defects in textile composite materials caused by the manufacturing process [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the researchers also found that defects such as holes, resin-rich regions, and fiber dislocations had a great impact on the mechanical properties of composites. Analyzing the influence of these defects on the failure behavior of materials was of great significance for the safe application of composite materials [ 25 , 26 , 27 , 28 ]. Previous researchers have conducted corresponding studies on the mechanical properties of 2.5D woven composites, from simple to complex, from two-dimensional to three-dimensional, and some research results have been obtained, which have laid a solid foundation for subsequent research [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%